Lung folding simulating peripheral pulmonary neoplasm (Blesovsky's syndrome). Issue 12 (December 1980) - Payne, C R; Jaques, P; Kerr, I H
Abstract : Six cases are reported in whom the diagnosis of benign pleural thickening with lung folding simulating peripheral pulmonary neoplasm was made. Three patients presented with chest pain, two were asymptomatic, and the abnormality was a chance finding in one patient with asthma. The radiographs in all cases showed similar appearances–a peripheral opacity appearing to lie within the lung, usually the lower lobe, and characteristic curvilinear shadows extending from the opacity to the hilum. At thoracotomy, predominantly visceral pleural thickening had caused the underlying lung to fold. Hyaline plaques were present on the parietal pleura elsewhere and pleural adhesions were usually absent. Adequate removal of the thickened visceral pleura in five patients allowed the folded lung to re-expand, with reversion of the chest radiograph to normal. One patient in whom the underlying lung folding was not appreciated at operation still has chest pain and the chest radiograph is unchanged. The radiographic appearances of this non-malignant condition, especially the appearances on lateral tomography, are diagnostic, and recognition may obviate the need for operation in asymptomatic patients. For those patients with chest pain, thoracotomy with removal of the visceral pleura and release of the folded lung appears to be effective in relieving this symptom.